Sequence-Based Characterization of Intratumoral Bacteria—A Guide to Best Practice - Walker, Sidney P.; Tangney, Mark; Claesson, Marcus J. (Frontiers in Oncology, 2020)
Tumors are hospitable environments to bacteria and several recent studies on cancer patient samples have introduced the concept of an endogenous tumor microbiome. For a variety of reasons, this putative tumor microbiome is particularly challenging to investigate, and a failure to account for the various potential pitfalls will result in erroneous results and claims. Before this potentially extremely medically-significant habitat can be accurately characterized, a clear understanding of all potential confounding factors is required, and a best-practice approach should be developed and adopted. This review summarizes all of the potential issues confounding accurate bacterial DNA sequence analysis of the putative tumor microbiome, and offers solutions based on related research with the hope of assisting in the progression of research in this field.